(untitled) (Medical Forum Monthly, 2023)
Objective: To measure and compare knee flexor strength at preoperative, three months, six months, and 12 months after surgery. Study Design: Analytic study Place and Duration of Study: This study was conducted at the Department of Orthopedics, KTH Peshawar, from January 2020 and January 2021. Materials and Methods: The connection between medial hamstring tendon graft harvest and knee flexor strength recovery after ACL repair was investigated in this study using a prospective cohort study methodology. Participants The Study involved 100 patients with medial hamstring tendon graft-assisted ACL restoration. Knee flexor strength was assessed by isokinetic dynamometry at the preoperative, three months, six months, and 12 months postoperative periods. Standardized surgical techniques carried out the graft harvest. Consistent adherence to rehabilitation techniques helped to reduce confounding variables. Demographic data were presented using descriptive statistics. Knee flexor strength, the primary end variable, was examined across various periods using repeated-measures analysis of variance (ANOVA). To pinpoint precise variations across time points, post hoc studies were carried out. Results: The Study group had a mean age of Z years and comprised X men and Y females. The distribution of graft types was as follows: semitendinosus (n%) and gracilis (n%). Sports-related injuries accounted for the bulk of injuries (n%). A significant interaction effect between time and graft harvest type was found by measuring the strength of the knee flexors (p 0.05). In particular, within the first six months after surgery, post hoc studies showed that patients who received medial hamstring tendon graft harvest displayed a delayed recovery in knee flexor strength relative to preoperative values. But with time, the power increased, nearing and sometimes exceeding preoperative levels at the 12-month point. Conclusion: During ACL repair, removing a medial hamstring tendon graft has a noticeable impact on the recovery of knee flexor strength. Knee flexor strength was shown to have short-term deficiencies, but the power steadily increased throughout postoperative therapy. These results highlight the need for customized rehabilitation plans and gradual activity progression to optimize knee flexor strength recovery after ACL repair with medial hamstring tendon grafts.